Boys R Us : Clique novel - Harrison, Lisi (New York : Poppy, Little, Brown and Company, 2009)
The members of the Clique face social drama, friendships, and challenges in this contemporary teen fiction novel.
Part of The Clique series.
Keywords: Teen fiction; Social life -- Juvenile fiction; Friendship -- Juvenile fiction; Contemporary realistic fiction